Análise multitemporal da silvicultura no estado de Goiás via sensoriamento remoto - Cabral, Escleide Gomes (2017)
Forestry is booming in Brazil due to demand for forest products. However, despite the importance of planted forests, forestry in the state of Goiás has been little studied. One of the reasons for the absence of studies in the state is due to the lack of disaggregated data and the great pulverization of the plantations, making it difficult to survey them. This work aimed to know the areas with commercial forest plantations, through remote sensing in the years 2002 and 2013, through the mapping carried out by Probio and TerraClass Cerrado, respectively, and in 2015 by the mapping carried out in this work, to assist in the Planning and development of state forestry. Analyzing the production and the values collected with the forest products in Goiás, we observed that some products have been replaced over the years by others, such as charcoal by wood chips, as well as other products that have been increasing in the production, such as firewood, which in the year 2000 obtained a production of 679,755 m³ and obtained a value of 6.6 million Reals. In less than 15 years, its production increased to 4,357,778 m³ of firewood. When we looked at the 2002, 2013 and the mapping of this study, we realized that there were important advances in the planted areas, so that in 2002 there were just over 500 ha of forest planted in Goiás; In 2013, were approximately 153 thousand ha; And in 2015, the area of forestry was 162,516 ha. The mesoregions with the largest commercial forest plantations are in the South, East and North, and the South and the East are the largest producers of wood and timber in the state of Goiás. The spatial distribution of eucalyptus plantations in Goiás Characterized by plantations in small areas and by a non-vertical production of the producers, reflecting the potential of forestry activity in income generation in small and medium farms and that despite the methodological differences used in the mappings used, the results were close to the results found for the current landscape of the state of Goiás elaborated in this work